Gender Differences in Extramarital Behaviors Among Couples in Long-Distance Marriages in the Digital Age: A Study in Kigali, Rwanda - Nkurunziza, Alphonse; Munganyinka, Claudine (Psympathic : Jurnal Ilmiah Psikologi, 2024)
This study investigated gender differences in extramarital behaviors in long-distance marriages, with a focus on the role of digital platforms in facilitating infidelity and the impact on marital commitment and satisfaction. The rationale for the study stems from the increasing prevalence of long-distance marriages in the digital age, where technology serves as both a means of maintaining connection and a potential risk factor for infidelity. A sample of 300 participants (150 men, 150 women) in long-distance marriages was recruited. Participants completed the Extramarital Behavior Scale (EBS), the Digital Communication and Infidelity Scale (DCIS), and the Marital Commitment and Satisfaction Scale (MCSS). Results showed that men reported higher levels of physical extramarital behaviors (mean = 3.2), while women exhibited more emotional extramarital behaviors (mean = 3.8). The use of digital platforms was strongly correlated with both physical (r = .55, p < .01) and emotional extramarital behaviors (r = .50, p < .01). Lower marital commitment (B = -.30, p = .002) and satisfaction (B = -.25, p = .038) were significant predictors of increased extramarital behaviors. In conclusion, digital platforms play a critical role in infidelity among long-distance couples, with notable gender differences in behavior patterns.